2022
DOI: 10.1021/acsbiomaterials.2c00702
|View full text |Cite
|
Sign up to set email alerts
|

Design of Cefotaxime Sodium-Loaded Polydopamine Coatings with Controlled Surface Roughness for Titanium Implants

Abstract: The success rate of dental implants is limited by peri-implant infection and insufficient osseointegration. Therefore, reducing the occurrence of peri-implantitis and promoting osseointegration are in demand. A roughened surface has commonly been applied to improve the osseointegration of implants, but it will accelerate the attachment of bacteria. We have developed novel antibiotic-decorated titanium (Ti) surfaces by the immobilization of dopamine and cefotaxime sodium (CS) simultaneously. Moreover, the surfa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 49 publications
0
1
0
Order By: Relevance
“…Investigators developed a biomimetic multilayer consisting of Ti–6Al–4V—Silver (Ag)—PDA and found that placing PDA as the top layer protected the Ag from corrosion and allowed for long-term sustained release, along with antibacterial activity against E. coli and Streptococcus aureus ( S. aureus ). Another study investigated the immobilization of dopamine and cefotaxime sodium (CS) onto the surface of Ti via copolymerization, which was able to prevent the adhesion and proliferation of E. coli and Streptococcus mutans ( S. mutans ) [ 50 ]. Mendhi and colleagues synthesized a PDA-based copper coating onto Ti that can regulate endogenous nitric oxide generation, leading to significant reductions in the biofilm metabolic activity and bacterial attachment paired with copper’s antimicrobial properties [ 51 ].…”
Section: Mussel Adhesive Proteins In Dentistrymentioning
confidence: 99%
“…Investigators developed a biomimetic multilayer consisting of Ti–6Al–4V—Silver (Ag)—PDA and found that placing PDA as the top layer protected the Ag from corrosion and allowed for long-term sustained release, along with antibacterial activity against E. coli and Streptococcus aureus ( S. aureus ). Another study investigated the immobilization of dopamine and cefotaxime sodium (CS) onto the surface of Ti via copolymerization, which was able to prevent the adhesion and proliferation of E. coli and Streptococcus mutans ( S. mutans ) [ 50 ]. Mendhi and colleagues synthesized a PDA-based copper coating onto Ti that can regulate endogenous nitric oxide generation, leading to significant reductions in the biofilm metabolic activity and bacterial attachment paired with copper’s antimicrobial properties [ 51 ].…”
Section: Mussel Adhesive Proteins In Dentistrymentioning
confidence: 99%